Manajemen Kelas: Upaya Mencapai Tujuan Hasil Belajar - Mustajib (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2020)
Education is a complex system and has many elements that must be in it. Among these elements are students and educators (teachers). In the learning process is certainly needed whose name is management related to the above elements. In this study will discuss class management so that the objectives of the learning process are achieved, which in it will be discussed; class management issues, class management objectives, class management implementation, and class management urgency. All of this is expected to make an effort to achieve satisfactory learning outcomes.